2021
DOI: 10.1186/s12981-021-00351-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression among adolescent with HIV/AIDS: a systematic review and meta-analysis

Abstract: Background Depression is particularly common among adolescents with HIV/AIDS and has been associated with disruption of the important developmental process, subsequently leading to a wide range of negative mental, physical and psychosocial consequences, as well as poor quality of life in those population groups. Nevertheless, to the best of our knowledge, there are no prior systematic reviews and meta-analytic studies that determined the prevalence of depression among adolescents with HIV/AIDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…More than 23% of the ALWHIV in the study reported current depressive episodes. Although this rate was a little lower than the 26% pooled prevalence reported in a global studies review [6], it is consistent with the pooled rate of 22% reported in those from sub-Saharan Africa [7]. In addition, 18.9% had an elevated risk of suicide, which is supported by an earlier study that reported 17% among children and adolescents attending a pediatric clinic in Uganda [22].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…More than 23% of the ALWHIV in the study reported current depressive episodes. Although this rate was a little lower than the 26% pooled prevalence reported in a global studies review [6], it is consistent with the pooled rate of 22% reported in those from sub-Saharan Africa [7]. In addition, 18.9% had an elevated risk of suicide, which is supported by an earlier study that reported 17% among children and adolescents attending a pediatric clinic in Uganda [22].…”
Section: Discussionsupporting
confidence: 87%
“…These findings thus reiterate the importance of focus on the psychological needs of ALWHIV, as they suffer from similar psychological disorders as the adult living with HIV [6,7]. Depressive disorders and suicidal behavior may impact HIV disease and quality of life [6,7], which makes it important to integrate routine screening into the treatment of ALWHIV.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations